Project Prioritization: Using BlueBikes Ridership and Spatial Network Analysis to analyze Boston-area Bicycle facilities - Brieff, Andrew. (Tufts University. Tisch Library., 2024)
Thesis (M.A.)--Tufts University, 2024.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Sumeeta Srinivasan.; Committee: Shan Jiang.; Keywords: Transportation, and Geographic information science and geodesy.